2021
DOI: 10.1371/journal.pone.0251886
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of patients with chronic obstructive lung disease and lung cancer in a public healthcare system

Abstract: Hypothesis There is limited data on the care and outcomes of individuals with both chronic obstructive pulmonary disease (COPD) and lung cancer, particularly in advanced disease. We hypothesized such patients would receive less cancer treatment and have worse outcomes. Methods We analyzed administrative data from the province of Ontario including demographics, hospitalization records, physician billings, cancer diagnosis, and treatments. COPD was defined using the ICES-derived COPD cohort (1996–2014) with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…We also found that many patients with COPD benefit from receiving adjuvant chemotherapy. Lung cancer patients with COPD have worse outcomes and are less likely to receive adjuvant therapy (39, 40). Additionally, lung cancer may be more aggressive in patients with COPD (41-43).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that many patients with COPD benefit from receiving adjuvant chemotherapy. Lung cancer patients with COPD have worse outcomes and are less likely to receive adjuvant therapy (39, 40). Additionally, lung cancer may be more aggressive in patients with COPD (41-43).…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of comorbid lung disease such as chronic obstructive pulmonary disease (COPD) has been associated with improved perioperative outcomes in patients with early-stage LC [24][25][26]. In fact, one study showed that co-diagnosis of COPD and LC is associated with less curative treatment in early-stage disease, less palliative treatment in advanced-stage disease, and overall worse outcomes [27,28]. Given the benefits of respiratory specialist assessment in LC care, it is possible that the increased likelihood of respiratory specialist management in patients managed through the LDAP had an influential role in contributing to the observed improved survival.…”
Section: Association Between Ldap Management and Treatmentmentioning
confidence: 99%
“…Overall survival is low in lung cancer patients with COPD (HR, 1.20; 95% CI, 1.19–1.22). Moreover, fewer surgical resections were performed and less adjuvant chemotherapy was administered to stage I or II lung cancer patients with COPD, and less palliative chemotherapy and radiation therapy were performed in stage III or IV lung cancer patients with COPD [ 27 ]. Active treatment for lung cancer might be limited because of the reduced lung function and breathing difficulty in COPD, which in turn leads to a decrease in the survival of lung cancer patients with COPD.…”
Section: Pulmonary Outcomesmentioning
confidence: 99%